Understanding Risk and Uncertainty Management: A Qualitative Inquiry into Developing Business Strategies Amidst Global Economic Shifts, Government Policies, and Market Volatility - Iriani, Nisma; Agustianti, Andi; Sucianti, Riska; Rahman M, Abdul; Putera, Wahyudi (Golden Ratio of Finance Management, 2024)
This research aims to investigate the management of risk and uncertainty within the context of developing business strategies amidst global economic shifts, government policies, and market volatility. The study employs a qualitative inquiry approach, utilizing systematic literature review and thematic analysis to identify emerging themes and patterns in contemporary business environments. The research findings reveal several key insights regarding adaptive strategies, scenario planning, and technological advancements in risk management. Firstly, adaptive strategies are crucial for organizational competitiveness and sustainability, emphasizing agility, innovation, and dynamic capabilities. Secondly, scenario planning facilitates strategic foresight, resilience, and preparedness by exploring alternative futures and assessing their potential impacts. Thirdly, technological advancements, particularly in AI and data analytics, revolutionize risk assessment capabilities and strategic decision-making processes, enabling proactive risk management and enhanced resilience. The study underscores the importance of fostering a culture of innovation, investing in technological capabilities, and integrating scenario planning into strategic planning processes to navigate uncertainties effectively. Moreover, future research directions include comparative analysis, longitudinal studies, cross-disciplinary research, technological innovation, crisis management, and ethical considerations to deepen understanding and promote effective strategies for organizational resilience and sustainability.